Eight plays for children : the new generation play project - Jennings, Coleman A., 1933- (Austin, Tex : University of Texas Press, 1999)
Contains eight plays for young people comissioned by a consortium of theaters, including Seattle Children's Theatre, The Children's Theatre Company of Minneapolis, Stage One: The Louisville Children's Theatre, and Honolulu Theatre for Youth; and features information about the history of the project, and comments by the playwrights.
Beauty and the beast / Constance Congdon -- Hula heart / Velina Hasu Houston -- East of the sun and west of the moon / Tina Howe -- The invisible man / Len Jenkin -- Kringle's widow / Mark Medoff -- Duke Kahanamoku vs. the surfnappers / Eric Overmyer -- Dogbrain / Michael Weller -- The witch of Blackbird Pond / Y. York.
Booklist.
University Press Titles (A.A.S.L./P.L.A.).
Young Adult
Keywords: Children's plays, American; Plays -- Collections; Children's plays; Drama -- Collections